Temporal resistance of potato tubers: Antibacterial assays and metabolite profiling of wound-healing tissue extracts from contrasting cultivars. (March 2019) - Dastmalchi, Keyvan; Perez Rodriguez, Mathiu; Lin, Janni; Yoo, Barney; Stark, Ruth E.
Abstract: Solanum tuberosum, commonly known as the potato, is a worldwide food staple. During harvest, storage, and distribution the crop is at risk of mechanical damage. Wounding of the tuber skin can also become a point of entry for bacterial and fungal pathogens, resulting in substantial agricultural losses. Building on the proposal that potato tubers produce metabolites to defend against microbial infection during early stages of wound healing before protective suberized periderm tissues have developed, we assessed extracts of wound tissues from four potato cultivars with differing skin morphologies (Norkotah Russet, Atlantic, Chipeta, and Yukon Gold). These assays were conducted at 0, 1, 2, 3 and 7 days post wounding against the plant pathogen Erwinia carotovora and a non-pathogenic Escherichia coli strain that served as a control. For each of the potato cultivars, only polar wound tissue extracts demonstrated antibacterial activity. The polar extracts from earlier wound-healing time points (days 0, 1 and 2) displayed notably higher antibacterial activity against both strains than the later wound-healing stages (days 3 and 7). These results support a burst of antibacterial activity at early time points. Parallel metabolite profiling of the extracts revealed differences in chemical composition at different wound-healing time points and allowed for identification of potential marker compounds according to healing stage for each of the cultivars. It was possible to monitor the transformations in the metabolite profiles that could account for the phenomenon of temporal resistance by looking at the relative quantities of various metabolite classes as a function of time. Graphical abstract: Highlights: Polar extracts from potato wound tissues showed antibacterial activity. Temporal resistance was confirmed by high activity of 0–2 day old wound tissue extracts. Phenolic amines and glycoalkaloids were the dominant metabolite classes. Increasing glycoalkaloid and decreasing phenolic amine proportions accompanied healing. Metabolite profile changes were distinctive for cultivars with contrasting skin russeting.